Shapers of English Calvinism, 1660 - 1714: variety, persistence, and transformation - Wallace, Dewey D. (Oxford studies in historical theology, 2011)
English Calvinism in a new era -- Peter Sterry: Calvinist mystic -- Theophilus Gale: Calvinism and the ancient theology -- Joseph Alleine: evangelical Calvinism -- Baxter, Bates, and Howe: Calvinist natural theology and "evidences" -- John Edwards: Church of England Calvinist